Highly Efficient Reduction of Aldehydes with Silanes in Water Catalyzed by Silver - Jia, Zhenhua; Liu, Mingxin; Li, Xingshu; Chan, Albert S. C.; Li, Chao-Jun (Synlett, 2013)
A highly efficient silver-catalyzed chemoselective method for the reduction of aldehydes to their corresponding alcohols in water was developed by using hydrosilanes as reducing agents. The ketones remained essentially inert under the same reaction conditions, thereby providing an additional synthetically useful chemoselectivity.
Keywords: aldehyde; reduction; silver; water